Stability Evaluation of Zinc Oxide Nanofluids Using Mangifera Odorata Extracted Peels and Leaves - Dilaeleyana Abu Bakar Sidik; Muhammad Zarif Daniel; Muhammad Faez; Muhammad Sufyan Naim; Amy Farhana Afiqah Azemi; Nuraina Syafiqah Md Rosdi; Nur Atiqah Syuhada Azuan (Journal of Science and Technology, 2025)
The most widely utilized materials to produce nanofluids (NFs) are metal oxides, which have limitations regarding dispersion stability. Producing stable NFs is a crucial step in enhancing their functionality in real-world applications. This study aims to determine the ideal conditions for NFs utilizing a more ecologically friendly technique by synthesizing zinc oxide (ZnO) NFs using Mangifera Odorata (MO) peel and leaves extract. The stability of NFs was assessed using an optical photograph, an ultraviolet (UV) – visible spectrophotometer, and a Fourier Transform Infrared Spectrophotometer (FTIR) under different conditions, including varying extracted MO to ZnO ratios and extracted MO pH. The results show that Zinc Oxide-Mangifera Odorata peel (ZnO–MOp) and Zinc Oxide–Mangifera Odorata leaves (ZnO–MOl) NFs at pH 8 and MO extract to ZnO ratios of 1:9 indicate the most stable NFs due to the low separation rate sedimentation over 18 and 24 hours of observation. Furthermore, it was discovered that the existence of Zn–O stretching functional groups was demonstrated by the strong peaks in the 585–590 cm?1 spectrum. These findings would eventually serve as a benchmark for future study, resulting in more stable and high-quality ZnO–MO NFs for use in wastewater treatment.